2003
DOI: 10.1007/s11745-003-1077-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of fish vs. formulations leads to higher plasma concentrations of n−3 fatty acids

Abstract: The n-3 fatty acids from fish appear to be more efficacious, in terms of cardioprotection, than equivalent amounts provided as capsules. Volunteers were given, for 6 wk, either 100 g/d of salmon, providing 383 mg of EPA and 544 mg of DHA, esterified in glycerol lipids, or 1 or 3 capsules of fish oil/d, providing 150 mg of EPA and 106 mg of DHA or 450 mg of EPA and 318 mg of DHA, as ethyl esters. Further, we reevaluated data from a previous study carried out with the same design, i.e., with 3 and 6 capsules/d o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
2
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 12 publications
10
97
2
5
Order By: Relevance
“…However, when we measured the n-3 PUFA content in plasma phospholipids, we observed a greater increase after consumption of the cod protein diet (from 5.74 Ϯ 0.29 to 8.62 Ϯ 0.21% of total fatty acids) than after consumption of the BPVEM diet (from 5.73 Ϯ 0.26 to 7.20 Ϯ 0.21% of total fatty acids) (P Ͻ 0.001), suggesting, as did Visioli et al (34), that n-3 PUFAs consumed in the form of fish could be more available than those consumed in the form of added fish oil. Most intervention studies in diabetic humans have reported no change in insulin sensitivity after n-3 PUFA supplementation of 2 weeks to 6 months (35,36).…”
Section: -Effects Of Cod Protein (Cp) Compared With Other Animal Protsupporting
confidence: 80%
“…However, when we measured the n-3 PUFA content in plasma phospholipids, we observed a greater increase after consumption of the cod protein diet (from 5.74 Ϯ 0.29 to 8.62 Ϯ 0.21% of total fatty acids) than after consumption of the BPVEM diet (from 5.73 Ϯ 0.26 to 7.20 Ϯ 0.21% of total fatty acids) (P Ͻ 0.001), suggesting, as did Visioli et al (34), that n-3 PUFAs consumed in the form of fish could be more available than those consumed in the form of added fish oil. Most intervention studies in diabetic humans have reported no change in insulin sensitivity after n-3 PUFA supplementation of 2 weeks to 6 months (35,36).…”
Section: -Effects Of Cod Protein (Cp) Compared With Other Animal Protsupporting
confidence: 80%
“…A useful approach may be to apply LCPUFA produced by certain species of marine algae that can be cultured industrially to provide the "fish" oil (Wen and Chen, 2003) as a promising alternative and contaminant-free source (Arterburn et al 2007). However, plasma LCPUFA concentrations after fish or fish oil capsule intakes showed that LCPUFA from fish were more effectively incorporated into plasma lipids than when administered as capsules (Visioli et al 2003). These issues may be of particular relevance during early development.…”
Section: Cardiovascular Outcomes-althoughmentioning
confidence: 99%
“…These data actually add to the notion that oligonutrients bioavailability is lower than such compounds isolated from their original matrix and administered as supplements (Visioli et al, 2003b).…”
Section: In Vivo Studiesmentioning
confidence: 67%